Scenario Writing of Future Lifestyles in Japan for 2030. (30th September 2016) - Tasaki, Tomohiro; Yoshida, Aya; Aoyagi, Midori; Kanamori, Yuko; Awata, Keigo; Tominaga, Naoki; Shimizu, Aiko; Suwabe, Hiromi; Nemoto, Kaori
Abstract: In order to change current lifestyles to sustainable ones, it is necessary to understand what kinds of lifestyle change could occur and what factors could affect these changes in the future. In this study, we explored possible lifestyle changes in Japan from the present to 2030, using techniques of scanning and constrained idea generation in an expert workshop. The participants generated 14 hypotheses for possible discontinuous changes by using a scanning technique wherein they skimmed many articles from different sources. Subsequently, the participants employed constrained idea generation, combining these ideas with continuous lifestyle changes to portray concept proposals for future lifestyles. Using these proposals, we elaborated four lifestyle scenarios and then investigated people's reactions to them. Finally, we discussed the insights obtained from this scenario writing in terms of attention needed to lifestyle scenario writing, similarity with other scenarios, and peoples' perceptions and transformation of lifestyles. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment